HIV seroconversion during pregnancy and the need for pre-exposure prophylaxis (PrEP) - Zorrilla CD (Dove Medical Press, 2018)
Carmen D Zorrilla,1 Fiorella Reyes Báez,1 Karolyn González Colón,2 Jessica Ibarra,2 Iris García,2 Ana M Mosquera2 1Obstetrics and Gynecology Department, University of Puerto Rico School of Medicine, San Juan, Puerto Rico; 2Maternal Infant Studies Center (CEMI), Obstetrics and Gynecology Department, University of Puerto Rico School of Medicine, San Juan, Puerto Rico Abstract: The reduction in the mother-to-infant transmission of HIV has been among the early successes of care and treatment of women living with HIV. Prenatal HIV counseling and testing, the availability of diverse antiretroviral therapies, elective cesarean section, and the use of formula milk have significantly reduced the mother-to-infant transmission in the USA and Europe. We are presenting two cases of seroconversion during pregnancy, identified during labor and delivery, of women who received risk reduction counseling and serial HIV testing during pregnancy. Because there are no guidelines for (or easy access to) the use of pre-exposure prophylaxis (PrEP) in pregnancy, they were offered other strategies for prevention including risk reduction counseling, condoms, and serial HIV testing. These cases support the use of PrEP during pregnancy. Both infants were negative and the women are currently receiving long-term highly active antiretroviral therapy. One of them recently delivered another infant. After these two women seroconverted, we decided to offer PrEP to all pregnant women presenting for care who report having an HIV positive partner. During the period 2012–2014, we treated ten HIV negative pregnant women who were partners of HIV positive men. Since 2015, we have seen 20 pregnant women in HIV discordant relationships. Of those, seven received PrEP. No seroconversions have been observed among the pregnant women on PrEP. Although small numbers, seroconversion during pregnancy was observed in two of 13 (15%) of the pregnant women in HIV-discordant relationships seen in our clinic, excluding those treated with PrEP. Given the safety data and experience with tenofovir and emtricitabine among pregnant women living with HIV, we believe PrEP should be offered in pregnancy and that guidelines should reflect this option as an additional strategy to reduce risks during pregnancy and to further reduce infant HIV transmission risk. Keywords: PrEP, pregnancy, HIV, HIV seroconversion